Os grupos tripartites parit??rios e a democracia deliberativa - Cavalheiro, Ruy Fernando Gomes Leme (2017)
The Brazilian tripartite process, in which representatives of the Government deliberate with representatives of employers and workers to revise and create regulations of the work conditions, is analysed in this study through the framework of J??rgen Habermas?? deliberative democracy theory. First the origins of the tripartite dynamics is established in the conseils de prud??hommes of XVIII century France, providing a model of workers and employers interaction that would influence the unionization of workers and their movement to obtain international laws regulating work conditions and the creation of a corresponding organization, which came to be the International Labour Organization (ILO). The unique tripartite method of composition and decision chosen by the ILO was integrated on their international conventions, and became one of their principles and international work basic rights. The development of tripartism in Brazil is registered since the creation of the Labour Justice until the recent adoption of tripartite consultations regarding the regulation of work conditions. Then the deliberative democracy theory of J??rgen Habermas is briefly and synthetically exposed, in a framework that shows its basic characteristics as a procedural dynamic centred on the rationality of discourse, which does not substitute institutionalized deliberation, but influences its decisions. Some interpretations of Habermas?? work are listed, and it is presented a synthesized list of it??s main elements. Based on these elements the regulatory process of the tripartite groups in Brazil is investigated thoroughly, and each of the items that characterize the habermasian theory is confronted with the corresponding tripartite dynamics procedure. The conclusion of the work is that the regulatory process of work conditions in Brazil can be considered a habermasian deliberative practice, despite specific discrepancies.